Stationary and Transient Simulations for a One-Dimensional Resonant Tunneling Diode (Communications in Computational Physics, 2008)
We investigate the validity of stationary simulations for semiconductor quantum charge transport in a one-dimensional resonant tunneling diode via fluid typemodels. Careful numerical investigations to a quantum hydrodynamic model revealthat the transient simulations do not always converge to the steady states. In particular,growing oscillations are observed at relatively large applied voltage. A dynamical bifurcation is responsible for the stability interchange of the steady state. Transient andstationary computations are also performed for a unipolar quantum drift-diffusionmodel.